Evaluation of salivary flow rate and salivary lactoferrin after radiotherapy of head and neck malignant neoplasms - Rogoleva-Gjurovski Sonja; Popovski Vladimir; Tošeska-Trajkovska Katerina; Kostadinova Lenče; Emin Melda (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: The most common postradiation complication in patients with head and neck neoplasms resulting from decreased salivary flow rate is xerostomia which affects the quality of life of patients in a negative way. On account of that, the application of volumetric modulated radiation therapy (VMAT) is found to be more precise in dose application, thus the surrounding healthy tissues can be spared from the negative influence of radiation. The aim of this study was to evaluate the salivary flow rate and salivary lactoferrin levels in patients with head and neck malign neoplasms following radiation therapy. Material and Methods: The research sample consisted of 24 patients treated with different radiation techniques, in which the salivary flow rate was measured for one minute. Additionally, the concentration of lactoferrin was quantitatively evaluated using biochemical analyses. Results: Higher average values were obtained in patients treated with a lower dose of radiation with up to 60 Gy, especially in those treated with a volumetric modulated radiotherapy technique. Therefore, from the results of linear correlation between the evaluated variables of lactoferrin and salivary flow volume in ml/min, it can be concluded that the correlation between these two variables is statistically significant whereby the correlation is negative with the coefficient of correlation r (24) = -0.903; (p < 0.01). Conclusion: The salivary flow rate is higher in patients treated with volumetric modulated radiotherapy, whereby the lower the dose of radiation, the higher the values of excreted saliva per minute. Therefore it can also be concluded that the higher values of lactoferrin are considered to have anti-inflammatory characteristics and are indicators of inflammation, which can be used for prevention of the salivary glands from negative effects of the radiation therapy.